1991
DOI: 10.1063/1.348842
|View full text |Cite
|
Sign up to set email alerts
|

Al induced crystallization of a-Si

Abstract: The crystallization of amorphous Si induced by Al during heat treatment has been investigated by cross section and plan view transmission electron microscopy. The lowest temperature of Al induced crystallization of amorphous Si was found to be 440 K. The crystallization temperature, however, depends on the thickness of Al layers in layered structures and on the concentration of Al in co-deposited layers below 1-nm-layer thickness and 15 at.% of Al concentration, respectively. Al-induced crystallization in laye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
77
0

Year Published

1997
1997
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 188 publications
(86 citation statements)
references
References 16 publications
2
77
0
Order By: Relevance
“…9 It has been reported that, in codeposited films of SiAl, which are a uniformly mixed state of amorphous Si and metal, the formation of metallic or metal-rich clusters is necessary before crystallization of amorphous Si. 10 The same effect could be considered as taking place with Si/Au or Ge/Au thin films. In this study, the intended value of the Au layer thickness of the thin films was 0.2 nm to 0.4 nm.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…9 It has been reported that, in codeposited films of SiAl, which are a uniformly mixed state of amorphous Si and metal, the formation of metallic or metal-rich clusters is necessary before crystallization of amorphous Si. 10 The same effect could be considered as taking place with Si/Au or Ge/Au thin films. In this study, the intended value of the Au layer thickness of the thin films was 0.2 nm to 0.4 nm.…”
Section: Resultsmentioning
confidence: 94%
“…Contact with a metal can drastically reduce the temperature at which amorphous Si or amorphous Ge crystallizes. [9][10][11][12] Figure 2a, b also shows XRD profiles of Ge/Au (0/4.8/0.2) and (0/4.6/0.4) thin films, as-deposited and annealed at various temperature. Both as-deposited samples (0/4.8/0.2) and (0/4.6/0.4) had broad amorphous phase profiles.…”
Section: Methodsmentioning
confidence: 95%
“…As a promising lowtemperature crystallization approach, metal induced crystallization (MIC) has been extensively studied. A layer of metal, for example, Al [1], Au [2], Ni [3], is deposited on top of a-Si and used as mediating layer to initiate the crystallization by forming nucleation centers in the low-temperature annealing process [4].…”
Section: Introductionmentioning
confidence: 99%
“…1 Introduction To reduce long processing times and high annealing temperatures the solid phase crystallization (SPC) of amorphous silicon (a-Si) has been modified to employ metals as catalysts for crystallization [1]. Known as metal induced crystallization (MIC) of silicon, the process was successful on a-Si or hydrogenated amorphous silicon (a-Si:H) grown by various deposition techniques, using both eutectic and non-eutectic metals [2].…”
mentioning
confidence: 99%